Student-teachers’ experiences in creating oral history texts - Azlina Abdul Aziz,; Jeyakumary Narayanasamy,; Maslawati Mohamad,; Hamidah Abdul Hameed, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The Malaysian government has announced the use of CEFR aligned English textbooks imported from the United Kingdom in schools. However, the use of imported textbooks faces much oppositions. The proponents of Malaysian based textbooks believe that English textbooks written in English should give due consideration to contents based on local setting. Thus, the researchers worked collaboratively with thirty, Year 3 Teaching English as a Second Language student-teachers who have enrolled in the course, Teaching Reading Skills in English as a Second Language. One of the course objectives is to produce an English supplementary book which consists of oral history texts with local context for lower secondary students. The research objective is to find out to what extent the student-teachers have gained from creating the oral history texts. This study employed a qualitative research approach adopting a case study method. Data were collected from a purposive sampling of 30 TESL student-teachers, who wrote the oral history texts. The research instruments employed were reflective journals, document analysis and interviews. The main findings show that the student-teachers gained valuable experiences in creating oral history texts for an ESL reading classroom. Besides some challenges faced, they gained a better realisation of the principles of teaching reading and material development in an ESL context. It is hoped that this study could give insights to the educators, policy makers and textbook writers in developing and using English textbooks with local contexts.